Morphological and molecular identification of cellulolytic fungi associated with local raru species - Deni Elfiati; ARIDA SUSILOWATI; CELVIA MODES; HENTI HENDALASTUTI RACHMAT (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Elfiati D, Susilowati A, Modes C, Rachmat HH. 2019. Morphological and molecular identification of cellulolytic fungi associated with local raru species. Biodiversitas 20: 2348-2354. This study is aimed to isolate and identify cellulolytic fungi from different local Raru species in Central Tapanuli, North Sumatra, Indonesia. Cellulolytic fungi are fungi that can degrade natural polymer materials such as cellulose. The fungal species were isolated from soil under three local raru species. The samples inoculating (1 mL) from serial dilutions (10-2 to 10-5) on Carboxy Methyl Cellulose (CMC) plates. The plates were incubated at 28 ?C for one week, then the fungal colonies were observed and pure cultures were maintained. Fungi with cellulolytic activity were characterized by the formation of clear zones around the colonies on CMC media plus congo red (0.1%). The identification of fungi was carried out by molecular identification of the isolated fungi at the species level. The extracted fungal DNA was amplified by PCR using specific internal transcribed spacer primer (ITS1/ITS4). The PCR products were sequenced and compared with the other related sequences in Gen Bank (NCBI). 20 isolates were successfully isolated and nine isolates had cellulolytic activity. Six fungal species from 20 isolates were identified as: Aspergillus sp., Penicillium sp., Aspergillus terreus, Penicillium mariae-crucis, Aspergillus tanneri and Penicillium citrinum. The results showed that Aspergillus terreus was the most abundant fungus obtained from all the raru stand.